2021
DOI: 10.1016/j.jamda.2020.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Step Numbers in Acutely Hospitalized Older Adults: The Hospital-Activities of Daily Living Study

Abstract: Objectives: To determine the number of steps taken by older patients in hospital and 1 week after discharge; to identify factors associated with step numbers after discharge; and to examine the association between functional decline and step numbers after discharge. Design: Prospective observational cohort study conducted in 2015e2017. Setting and Participants: Older adults (!70 years of age) acutely hospitalized for at least 48 hours at internal, cardiology, or geriatric wards in 6 Dutch hospitals. Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 48 publications
(63 reference statements)
4
32
1
1
Order By: Relevance
“…After discharge a doubling in uptime was seen. Our findings are consistent with a recent study by Kolk et al [ 57 ], which aimed to measure the number of steps taken per day in hospital and up to one week after discharge in 188 old (+70) acutely hospitalized patients, with Fitbit Flex worn on the wrist. In contrast, their study did not measure the distribution of physical activity and sedentary through the day.…”
Section: Discussionsupporting
confidence: 93%
“…After discharge a doubling in uptime was seen. Our findings are consistent with a recent study by Kolk et al [ 57 ], which aimed to measure the number of steps taken per day in hospital and up to one week after discharge in 188 old (+70) acutely hospitalized patients, with Fitbit Flex worn on the wrist. In contrast, their study did not measure the distribution of physical activity and sedentary through the day.…”
Section: Discussionsupporting
confidence: 93%
“…Another starting point for the effort to increase patients' physical activity during hospitalization could be to encourage physical activity around 10-11 AM, 3 PM, and 5-6 PM, which would be more consistent with their habitual. Our ndings are also consistent with a recent study by Kolk et al [54], which showed a doubling in steps only one day after discharge compared with one day prior to discharge. Presumably, the relatively high level of activity after discharge in our study, with a median of 2207 steps per day after discharge and 2622 four weeks after discharge, indicates that patients' return to their basic routines occurs earlier than expected, our results indicate a recovery of activity the rst week after discharge.…”
Section: Baseline Characteristicssupporting
confidence: 93%
“…Furthermore, physical activity assessed postdischarge is likely a better determinant of future ADL and IADL trajectories as it is free of the previously mentioned hospitalassociated barriers. Therefore, future studies should incorporate physical activity and sedentary behavior assessment postdischarge, as is being highlighted using data of the Hospital-ADL cohort of acute patients, 48 and include more distant follow-up to evaluate the longterm role of physical activity during and posthospitalization.…”
Section: Discussionmentioning
confidence: 99%